2003
DOI: 10.1097/00004650-200307000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Reiki Therapy

Abstract: This study evaluates how nurses who gave Reiki therapy perceived the benefit of this therapy on their clients and on themselves concurrently as providers of the therapy. As an adjunct, the study's purpose was to enhance the understanding and credibility of nurse/Reiki practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(8 citation statements)
references
References 4 publications
0
5
0
3
Order By: Relevance
“…The use of Reiki in treating nurses with stress-related problems has been documented in several studies. 11 - 14 Diaz-Rodrigues et al found that a single Reiki session can improve immune function and blood pressure regulation. 13 In a phenomenological study of 8 nurse/Reiki masters, seven themes were developed showing the benefits received by the practitioner during a Reiki client therapy session, including feeling more peaceful, calm, and relaxed; handling stress and anxiety better; helping the client's healing process; and an increased satisfaction with being a nurse/Reiki practitioner as compared with previous or present nursing work.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The use of Reiki in treating nurses with stress-related problems has been documented in several studies. 11 - 14 Diaz-Rodrigues et al found that a single Reiki session can improve immune function and blood pressure regulation. 13 In a phenomenological study of 8 nurse/Reiki masters, seven themes were developed showing the benefits received by the practitioner during a Reiki client therapy session, including feeling more peaceful, calm, and relaxed; handling stress and anxiety better; helping the client's healing process; and an increased satisfaction with being a nurse/Reiki practitioner as compared with previous or present nursing work.…”
Section: Background and Significancementioning
confidence: 99%
“… 13 In a phenomenological study of 8 nurse/Reiki masters, seven themes were developed showing the benefits received by the practitioner during a Reiki client therapy session, including feeling more peaceful, calm, and relaxed; handling stress and anxiety better; helping the client's healing process; and an increased satisfaction with being a nurse/Reiki practitioner as compared with previous or present nursing work. 14 Reiki level-1 training improves nurses' beliefs around their caring behaviors at the bedside. 11 Additionally, Reiki level 1 is associated with reductions in work-related stress levels as measured by the Perceived Stress Scale in a pilot study.…”
Section: Background and Significancementioning
confidence: 99%
“…Nurses may easily learn Reiki therapy and use this intervention with patients in day-to-day practice (Whelan & Wishnia, 2003). Additionally, Reiki therapy may be a good self-care tool as suggested by more than one study (Cuneo et al, 2011; Diaz-Rodriguez et al, 2011; Vitale, 2009).…”
Section: Implications For Nursing Education Practice and Researchmentioning
confidence: 99%
“…In many studies, it has been reported that Reiki, applied for special purposes, has such effects as reducing stress, emotional distress, and fatigue, maintaining healthy circulation, regulating autonomic nervous system activity, restoring comfort, and therefore improving well-being. [15][16][17][18][19][20][21][22] Based on the results of these studies, it is assumed that Reiki practice can be effective in reducing the stress and fatigue that nurses experience during these compelling processes. Again, in another study, it was determined that Reiki applied to health professionals has positive effects on the parasympathetic system.…”
mentioning
confidence: 99%
“…It has been reported that the healing effect of Reiki is realized by encouraging the body's self-healing through ways such as rebalancing the biofield of the energy flowing during the application, regulating the parasympathetic nervous system activity, and strengthening the ability to increase the systemic resistance against the destructive effect of cortisol, which is released during stress. In many studies, it has been reported that Reiki, applied for special purposes, has such effects as reducing stress, emotional distress, and fatigue, maintaining healthy circulation, regulating autonomic nervous system activity, restoring comfort, and therefore improving well-being 15–22. Based on the results of these studies, it is assumed that Reiki practice can be effective in reducing the stress and fatigue that nurses experience during these compelling processes.…”
mentioning
confidence: 99%